Radical Hysterectomy with Pelvic Lymphadenectomy: Indications, Technique, and Complications - Rachel A. Ware; John R. van Nagell (Obstetrics and Gynecology International)
Radical hysterectomy with pelvic lymphadenectomy remains the treatment of choice for women with Stages IA2 and IB1 carcinoma of the cervix, and selected patients with Stage II endometrial cancer. Improvement in surgical techniqe, administration of prophylactic antibiotics, thromboemolic prophylaxis, and advances in critical care medicine have resulted in lower operative morbidity associated with this procedure. Major urinary tract complications such as ureteral injury or vesico-vaginal fistula are now extremely rare (<1%). Five-year survival rates following this procedure vary according to a number of clinical and histologic variables, and may be as high as 90% in women without lymph node metastases.